2012
DOI: 10.1016/j.bone.2012.02.445
|View full text |Cite
|
Sign up to set email alerts
|

Fractures in users of antidepressants and anxiolytics and sedatives effects of age and dose

Abstract: Aim-To study the effects of age and dose of selective serotonin reuptake inhibitors (SSRI), trycyclic antidepressants (TCA) and anxiolytics/sedatives on fracture risk. Subjects and methods-Case control study. From the Danish National Health Service, we identified 124,655 fracture cases and 373,962 age-and gender-matched controls. Crude odds ratios (OR) were estimated, and propensity score adjustment was used to minimize confounding by indication. Results-A higher risk of fractures was associated with an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…In the 11 case‐control studies, the numbers of case and control subjects ranged from 34 to 14 958 and from 412 to 373 962, respectively. In the 22 cohort studies, the numbers of participants ranged from 18 to 906 422 and the mean follow‐up period from 6 months to 10 years .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 11 case‐control studies, the numbers of case and control subjects ranged from 34 to 14 958 and from 412 to 373 962, respectively. In the 22 cohort studies, the numbers of participants ranged from 18 to 906 422 and the mean follow‐up period from 6 months to 10 years .…”
Section: Resultsmentioning
confidence: 99%
“…11,18,19,31,[40][41][42][43][44][45][46][47][48][49][50][51][52] The studies we found were published between 1998 37 and 2016, 19,[42][43][44]49 with 11 studies since 2013. 11,19,40,41,[43][44][45][46]48,49,52 Two studies were reported across multiple articles and each was treated as a single distinct study: Vestergaard et al 21,53,54 and Souverein et al 49,55,56 One study reported results from both a cohort 49,55 and a nested case-control analysis. 49,56 Estimates of effect size were very similar, but for meta-analyses where both sets of results were available, we kept those from the cohort analysis, as precision was higher, and dropped the case-control results.…”
Section: Resultsmentioning
confidence: 99%
“…Lower scores indicated poorer physical function. Barthel index scores were categorized as per Wade and Collin [52] classifications: total dependence (0-4), severe dependence (5)(6)(7)(8)(9)(10)(11)(12), moderate dependence (13-18), mild dependence (19) and total independence (20).…”
Section: Physical Function Measurementioning
confidence: 99%
“…Third, we were not able to analyse the relationship between different doses of SSRIs and the risk of fractures, since there was little variation in the dose prescribed to the vast majority of our patients (and most were prescribed doses similar to those recommended for the treatment of depression). A recent population-based case–control study in Denmark suggests that fracture risk depends on average daily dose, but since average daily dose and cumulative dose were not disentangled, it is not clear whether daily dose is an independent predictor of fracture risk beyond its contribution to cumulative dose 35. Lastly, although we achieve good balance across known confounders, unmeasured confounding may still exist.…”
Section: Discussionmentioning
confidence: 87%